Exercise therapy for trismus secondary to head and neck cancer: A systematic review. Issue 1 (15th February 2016) - Kamstra, Jolanda I.; van Leeuwen, Marianne; Roodenburg, Jan L.N.; Dijkstra, Pieter U.
Abstract: Background: Effects of exercise therapy for trismus secondary to head and neck cancer have not been reviewed systematically since 2004. Methods: Four databases were searched. The quality of observational studies and randomized controlled trials was assessed. Results: Two hundred eleven articles were found, 20 studies were included. A large variation in research methodology, stretching techniques, duration of stretch, and repetition of exercises was found. The overall quality was moderate. Five of the 8 preventive studies found that exercises during (chemo)radiotherapy could not prevent a reduction in mouth opening. In 4 therapeutic case studies, mouth opening increased between 17 and 24 mm. In 8 other therapeutic studies, mouth opening increased between −1.9 and 13.6 mm. No exercise therapy was clearly superior to the others. Conclusion: Changes in mouth opening ranged considerably and no stretching technique was superior to others regarding either prevention or treatment of trismus. Clinical guidelines cannot be given based on this systematic review. © 2016 Wiley Periodicals, Inc. Head Neck 39: 160–169, 2017